Major Factors Contributing to the Failure of Digitalization in the Public Sector Organizations: An Analysis of the Federal Government of Pakistan (Journal of Asian Development Studies, 2024)
Pakistan is a developing country with rather traditional and outdated models of governance that does not effectively correspond to the postmodern practices of electronic and digitalized governance. A majority of initiatives aimed towards incorporation of Information Communication Technology (ICT) in the public sector are not satisfactorily implemented and do not bear positive impacts for improving public service. The purpose of this paper to analyze and understand the factors the contribute to the failure in implementation of the initiatives and projects aimed to incorporate ICT and digitalization in the public sector of Pakistan. The paper scrutinizes this state of affairs through interviews and survey questionnaires targeted towards high ranking officials of the public sector and associated government departments and authorities. This paper is of quantitative nature and has been facilitated through interviews, surveys and questionnaires. The findings demonstrate that despite considerable continued efforts, prevailing predicaments of inflexible red tape, paucity of financial resources, incompetence of public sector staff and unstable political scenario are factors that hinder the progress of digitalization. This is a major gap identified in this paper. Furthermore, the paper also suggests and recommends practical solutions to cope with these problems, including political solutions and recommendations for financial problems.